The Students' Perception of English Teachers' performance in teaching at the second grade students of MTs in Kecamatan Somba Opu - Hasniar Hasniar; Sitti Nurpahmi (ELTIES : English Language Teaching for EFL Learners, 2023)
AbstractThis research was aimed to know the students’ perception on the English teachers’ performance in teaching at the second grade students of Madrasah Tsanawiyh in kecamatan Somba Opu Gowa English at several schools of Madrasah Tsanawiyah in Gowa Regency. The researcher used descriptive quantitative in acquiring the result of questionnaire, which aimed to find out the students’ perception on English teachers’ performance of each Madrasah Tsanawiyah at kecamatan Somba Opu Gowa. The samples of this research were the second grade students of each school which totally consisted of 120 students and the English teachers of each school which consisted of 8 teachers. These schools were MTs. Guppi, MTs. Ashshaihin, MTs. Madani, MTs. Bani rauf, MTs. Manggaruppi, MTs. Nurfadilah, MTs. Syekh Yusuf and MTs. Aisyiyah. The instruments of this research was questionnaire. The questionnaire was used to know how the students’ perception was based on Engish teachers performance in teaching. The findings of this research showed that the mean score of students’perception on teachers’ performance in teaching English at Madrasah Tsanawiyah in kecamatan Somba Opu Gowa was in interval scale between 145.78-157.332 which means “Positive Perception”.Those results indicated that the English teachers’ performance in teaching were qualified good category, which the mean score of Students’ perception was 45.83%. Based on the results of this research, the researcher found that English Teachers’ Performance on teaching at Madrasah Tsanawiyah in kecamatan Somba Opu obtained positive perception. Therefore, it was suggested that teachers should present good material to make the students more interested in learning, because the teaching material influenced to the students understanding. The teachers also had to know what students’ difficulties in learning English are, and help to solve their problem. Furthermore, the teachers should also apply games more in teaching. Keywords: Students’ perception, Teachers’ Performance, MTs Gowa.